Investigation of Dendrimer Structures by Means of K-Banhatti Invariants - Cheng-Gang Huo; Fozia Azhar; Abaid Ur Rehman Virk; Tariq Ismaeel (Journal of Mathematics)
Dendrimers are highly branched macromolecules. The structural chemistry of dendrimers could be shaped by their topological invariants to target the particular design with appropriate properties to bring the drugs to mark a carrier vehicle. This study is about some new topological indices of dendrimer generations. Here, we calculate K Banhatti indices for five generations of dendrimers. Precisely speaking, we computed the 1st K Banhatti redefined Zagreb index, 2nd K Banhatti redefined Zagreb indices, and 3rd K Banhatti redefined Zagreb index for the dendrimers Dip for i=1,2,3,4,5.